2015
DOI: 10.1104/pp.15.00596
|View full text |Cite
|
Sign up to set email alerts
|

ABA-regulation of root hydraulic conductivity and aquaporin gene- expression is crucial to the plant shoot rise caused by rhizosphere humic acids

Abstract: The physiological and metabolic mechanisms behind the humic acid-mediated plant growth enhancement are discussed in detail. Experiments using cucumber (Cucumis sativus) plants show that the shoot growth enhancement caused by a structurally well-characterized humic acid with sedimentary origin is functionally associated with significant increases in abscisic acid (ABA) root concentration and root hydraulic conductivity. Complementary experiments involving a blocking agent of cell wall pores and water root trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
73
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 44 publications
9
73
1
1
Order By: Relevance
“…This action results from the HS capacity to improve plant nutrient availability in soil, mainly through the formation of stable complexes with metals (Chen et al, ; Erro et al, ; Garcia‐Mina, ; Gerke, ; Urrutia et al, ). Besides this effect on improving nutrient bioavailability, HS also promotes plant growth through action on plant metabolism and physiology, which is derived from the interaction of HS with plant roots (Canellas, Olivares, Okorokova‐Facanha, & Facanha, ; Muscolo, Sidari, Francioso, Tugnoli, & Nardi, ; Olaetxea et al, , ; Quaggiotti et al, ). However, knowledge about the mechanisms responsible for this direct effect of HS on the promotion of plant growth is scarce and fragmentary, regarding the effects on both root development and shoot development (García et al, ; Mora, Bacaicoa, Baigorri, Zamarreño, & García‐Mina, ; Olaetxea et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This action results from the HS capacity to improve plant nutrient availability in soil, mainly through the formation of stable complexes with metals (Chen et al, ; Erro et al, ; Garcia‐Mina, ; Gerke, ; Urrutia et al, ). Besides this effect on improving nutrient bioavailability, HS also promotes plant growth through action on plant metabolism and physiology, which is derived from the interaction of HS with plant roots (Canellas, Olivares, Okorokova‐Facanha, & Facanha, ; Muscolo, Sidari, Francioso, Tugnoli, & Nardi, ; Olaetxea et al, , ; Quaggiotti et al, ). However, knowledge about the mechanisms responsible for this direct effect of HS on the promotion of plant growth is scarce and fragmentary, regarding the effects on both root development and shoot development (García et al, ; Mora, Bacaicoa, Baigorri, Zamarreño, & García‐Mina, ; Olaetxea et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies using the DR5::GUS construct (a genetic construct where the synthetic auxin‐responsive promoter DR5 controls the expression of bacterial β‐ d ‐glucuronidase) (Bierfreund, Reski, & Decker, ) in several plant species showed that the application of HA to the roots induced the upregulation of genes controlled by auxin‐dependent signaling pathways (Trevisan, Pizzeghello, et al, ). These effects were also linked to NO‐ and ethylene‐dependent signaling pathways (Mora, Baigorri, Bacaicoa, Zamarreño, & García‐Mina, ; Zandonadi et al, ), as well as to significant increases in root plasma membrane (PM) H + ‐ATPase activity and root ABA concentration (Canellas et al, ; Mora, Bacaicoa, et al, ; Mora et al, ; Olaetxea et al, ; Zandonadi et al, ). Some authors have proposed the hypothesis that the HA‐mediated increase in root development may result from a coordinated effect on proton and Ca 2+ effluxes associated with root PM H + ‐ATPase activity under the “acid‐growth theory” (Ramos et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abscisic acid (ABA) regulates plant water status, and promotes seed maturation and dormancy. Under drought stress conditions, ABA inter alia triggers stomatal closure, thus minimizing the loss of water through transpiration (Merilo et al ., ), and changes hydraulic conductivity in a dose‐dependent manner (Dodd, ; Olaetxea et al ., ) as well as modulates root system architecture to improve water uptake (Harris, ). ABA is also well‐recognized as a repressor of seed germination.…”
Section: Introductionmentioning
confidence: 99%